Turun Melayu: Konstruksi Identitas Orang Dayak Muslim di Desa Kuala Rosan Kalimantan Barat - Af’idatul Lathifah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2018)
The province of West Kalimantan is known as a province inhabited by Dayak etnhnic. However, it cannot be denied that Malay also became the ethnic group dominated the province. The existence of Malay also  brings new religion to Dayak, namely Islam. The conversion of the Dayak religion into a Muslim certainly has cultural consequences. Dayak customs that are in part contrary to Islamic teachings must certainly be abandoned. Going down to Malays is the choice of Dayaks when they embrace Islam. Religious conversion is also followed by the conversion of culture, thus forming a new cultural community that is different from the Dayak and at the same time different from the Malays.